A Main Belt Asteroid: the Most Probable Cause of the Tunguska Event - Jopek, Tadeusz J.; Gonczi, Robert; Froeschle, Christiane; Michel, Patric; Longo, Giuseppe; Foschini, Luigi (Societa Astronomica Italiana, 2002)
We studied the available scientific literature on the Tunguska event of 30 June 1908 to select a sample of atmospheric trajectories. Then we calculated a set of parameters from which we obtained 886 orbits. Using the model of Bottke and colleagues on dynamical properties of celestial bodies, we estimated the probabilities of different origins of the Tunguska Cosmic Body (TCB). Event though 6 of 886 orbits can be both asteroidal or cometary, the probability of an asteroidal origins remain s the highest.
Keywords: Tunguska